Pharmacological potential of Sargassum sp. of west coast of Maharashtra Kunkeshwar, India - Abdi, Gholamreza; Karande, Vanita Chandrashekhar; Mohammed, Arifullah; Abbasi Tarighat, Maryam; Wen Goh, Khang; Abdul Kari, Zulhisyam; Seong Wei, Lee; Ahmad Mohd Zain, Muhammad Rajaei; Mohammadi, Mehdi; Ee Lee, Gaik; Barwant, Mukul M. (Frontiers in Marine Science, 2022)
A promising plant group that is important in medicine is the seaweed. In this investigation, we have focused on the pharmacological prospects of brown algae (Sargassum sp). Nutraceuticals refer to products that may combine pharmacological and nutrition. We have collected the plant material close to Kunkeeshwar in Sindhudurg, Maharashtra’s western coast. We focused on the Physicochemical Attributes of Sargassum sp., and the study found that the ash value (41 ± 0.67), moisture content (1.33 ± 0.038), alcohol-soluble extractive value (1.5 ± 0.030), moisture content (1.33 ± 0.038), and total cash value (41 ± 0.67) are all stated in (%).The GCMS findings, which demonstrate that a total of 25 chemicals were discovered in the aqueous extract of Sargassum sp., also represent their nutritional profile. All of these substances have chromatograms that can be observed.1-Hexyl-2-nitrocyclohexane is the substance with the second-largest retention duration and relative areas, followed by n-hexadanoic acid. The presence of ocladecanoic acid was later determined. The explanation for how the activity is concentration-dependent is pharmacological activity, particularly antioxidant activity as shown by the DPPH assay.2μg/mL is -1545.4 ± 0.05. as a minimum. and at (32 g/mL is 7.67 ± 0.05) is the highest. The antifungal activity of Candida albicans (12.8 mm) and Aspergillus niger (14.4 mm) both exhibit zone inhibition when tested against two distinct pathogen however, the antibacterial activity of three different bacteria demonstrates that Staphylococcus aureus (12 mm), Bacillus subtilis (10 mm), Proteus mirabilis (12.8 mm), and Escherichia. coli are all zone inhibited (13mm). Brown algae offer the greatest potential for human health nutrition, while pharmacological analysis is helpful for therapeutic application, according to the overall analysis.